Work roll shifting method by optimum calculation of work roll profile in hot strip rolling. (2017) - Yamaguchi, Shinya; Miyake, Masaru; Kimura, Keisuke; Jinnouchi, Tatsuya
Abstract: In hot strip rolling, the work roll shifting method has been widely used to disperse thermal crown and wear of the work rolls in the axial direction. This paper provides a strategic control method for the work roll profile which surpasses the conventional work roll shifting method. A numerical simulation model which enables prediction of thermal crown and wear of work rolls with high accuracy has been developed, and a new shifting method has been proposed, focusing on the problems of the conventional shifting method. In the conventional shifting method, the work roll shift position follows the prearranged pattern, and the work roll profile is not controlled intentionally. On the other hand, in a new work roll shifting method, the work roll profile of all coils in the rolling campaign are predicted by the numerical calculation, and controlled so as to be equal to the target profile by considering the work roll shift position. An evaluation function consisting of the error between predicted work roll profile and the target profile of all coils in the rolling campaign has been used, and the work roll shift position has been decided by the optimum calculation with minimizing the evaluation function.